Conceptualizing Academic Library Use: Results of a Survey of Continuing Education Students in a Small Canadian Undergraduate University - Williams, A. Paul (Canadian Journal of Higher Education, 1995)
This paper analyzes data from a survey of 4,084 continuing education students in a small Canadian undergraduate university to document and conceptualize patterns of library services use and factors influencing use. Factor analysis, multiple regression and analysis of variance are employed to examine the impact of three sets of explanatory variables on academic library use: student characteristics (e.g., age, sex and previous education); perceptions of problems limiting library use; (e.g., the adequacy of the collection, hours, and access to materials); and characteristics of the student's program of study (e.g., field of study, type of program, number of library-related assignments). The findings show that the most frequently used university library services, accounting for almost half of all use, were the study areas and the photocopy machines. The characteristics of the student's program of study including the extent to which library use was integrated into assignments and classroom discussion was found to be a strong predictor of use. The paper concludes that when conceptualizing and planning library services greater attention must be given to the broader learning environment of which the library is part and to the characteristics and needs of increasingly diverse student populations.